Peer Guidance as a Adolescent's Emotional Literacy Development Strategy - Karsih Karsih; Ahman Ahman; Mamat Supriatna (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2019)
The study aims to determine the effectiveness of peer guidance strategies to improved emotional literacy in adolescents. The study used an experimental research type with two groups, pretest-posttest, with control group design. The sampling technique used was purposive sampling and random assignment. The experimental group and the control group each consisted of two groups, each consisting of five participants. The study used an emotional literacy questionnaire to determine the level of emotional literacy in adolescents. The data analysis technique used the Mann Whitney U Test. The study results showed that the story writing technique is effective in improving adolescents' emotional literacy. Counselors can use study results to help adolescents improve emotional literacy through peer guidance strategies.